CsWRKY29, a key transcription factor in tea plant for freezing tolerance, ABA sensitivity, and sugar metabolism - Chengjin Xue; Xiaozhen Huang; Yichen Zhao (Scientific Reports)
Abstract Tea plants (Camellia sinensis L.) are prone to spring frosts, leading to substantial economic damage. WRKY transcription factors are key in plant abiotic stress responses, yet the role of CsWRKY29 in freezing tolerance is unclear. In this study, quantitative real-time PCR (qRT-PCR) and transient green fluorescent protein assay revealed that CsWRKY29 localizes to the nucleus and its expression is induced by cold and abscisic acid (ABA). CsWRKY29 overexpression in Arabidopsis enhanced freezing tolerance, reduced electrolyte leakage, increased soluble sugars, and boosted superoxide dismutase activity, with upregulated COR genes. These lines also showed heightened ABA and glucose sensitivity. Cold treatment of CsWRKY29-overexpressing lines upregulated AtABI5, AtHXK1, and AtSUS4 compared to wild type, and yeast one-hybrid assays confirmed CsWRKY29 binding to the W-box in the CsABI5 promoter. Furthermore, the application of virus-induced gene silencing (VIGS) technology to reduce CsWRKY29 expression in tea plants revealed a significant decrease in the transcript levels of CsCBFs, CsABI5, CsHXK1, and CsSUS4 in the silenced plants. In summary, our findings indicate that CsWRKY29 may serve as a critical transcription factor that contributes to freezing tolerance, ABA responsiveness, and sugar metabolism within tea plants.